Counter-Terrorist Financing (CTF) regimes and institutional responses: a case study of Boko Haram insurgency in Nigeria - Obonyilo, Matthew (Department of Public Law, 2026)
This thesis examines the intricate process of transmitting United Nations Security Council Resolutions 1267 and 1373 to Nigeria and operationalising global counter-terrorist financing policies through legal frameworks and a matrix of security and other state institutions in the domestic environment. The investigation focuses on the complex dynamics of the transmission process, from international to national, and inter-institutional diffusion involving internal institutions in Nigeria as a developing state. By critically engaging Michael Boyle's contributions to our understanding of how local contexts and situational specificities impact the effective transmission and diffusion of international counter-terrorism policies, the study considers how Nigeria's local conditions impact efforts to limit Boko Haram's access to funding through international regulatory instruments on counter-terrorist financing. The study both confirms and augments Boyle's analysis by drawing on qualitative field data involving nineteen policy specialists attached to governance and security elites in Nigeria and three multilateral institutions: United Nations Office on Drugs and Crime (UNODC), Financial Action Task Force (FATF), and Inter-Governmental Action Group against Money Laundering in West Africa (GIABA). Although the study demonstrates the applicability of Boyle's theory to Nigeria's conflict landscape, it rejects the idea that associates the failures of international counter-terrorism policies in third-world countries solely with the peculiarities of the domestic environment. The study sought to carve out space for other variables beyond Boyle's local conditions. They are those linked to development dynamics –corruption and underdevelopment, and global geo-political calculus - international assistance, international regulation, and the politics of the global war on terror. The study argues that to arrive at a more comprehensive understanding regarding counter-terrorism outcomes in a non-Western context, an overarching framework of formative influences in both the domestic environment and at the global governance level gives more profound insights into the issues impacting the effectiveness of counter-terrorism measures in a non-Western environment like Nigeria.